Document Falsification/Forgery from the View of Islamic Jurisprudence and Malaysian Law - Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin; Lukman Abdul Mutalib; Muneer Ali Abdul Rab al-Qubaty (Al-Jami'ah: Journal of Islamic Studies, 2019)
Although the scholars of Islamic jurisprudence discussed the importance of document and its strength as a mean of proof, they did not discuss the issue of forgery unless slightly compared with the scholars of law. This is due to its limited extension and uses in the period of times. And with the frequent use of them in our time, the debates have extended towards several circumstances either to attempt for or to deny a forgery. Therefore, this research is conducted to study the document falsification from the perspectives of Islamic Jurisprudence and Malaysian Law. It is also to explain the definition, procedure and methods to identify the crime and its punishment. The study used inductive and content analysis methods on previous scholars’ opinions, discussions and explanation from two different legal institutions. This study found the following important results: The are many forms of forgery occur in this era and can be classified either as material or incorporeal fraud. Several implications have been issued against the forgery crime in the Malaysian Penal Code, such as imprisonment, lashes and fines. The Islamic jurisprudence and the Malaysian Evidence Act 1950 has established several methods to verify the validity of documents such as confession, testimony, expert opinion, and oath, but the opinion of the expert is the most important means in verifying the authenticity and originality of documents. This study also found that the Malaysian Evidence Law did not discuss the oath as a mean to verify documents. As analysed, the method to verify documents discussed in the books of jurisprudence is very different from that of the Malaysian Evidence Act 1950, which specifies the conditions of documents and the number of witnesses, but the law does not specify the number of witnesses and impose conditions only.[Meskipun para ahli tata hukum Islam membahas pentingnya sebuah dokumen sebagai alat bukti, namun mereka kurang membahas persoalan pemalsuan dokumen sedalam para ahli hukum konvensional. Hal ini terkait dengan terbatasnya waktu dan kuantitas penggunaan, sehingga frekuensi penggunaannya memunculkan debat yang panjang, baik yang menerima atau yang menolak soal pemalsuan. Oleh karena itu, artikel ini membahas pemalsuan dokumen dari perspektif tata hukum Islam dan hukum nasional di Malaysia. Artikel ini juga menjelaskan definisi, prosedur, dan metode identifikasi kejahatan ini serta hukumannya. Penulis menggunakan metode induktif dan analisis isi pada opini, perdebatan, dan penjelasan dari dua institusi hukum yang berbeda. Kajian ini menyimpulkan adanya beragam bentuk pemalsuan dewasa ini, baik material atau non material. Beberapa aturan hukum telah dikeluarkan di Malaysia dan sangsi nya seperti penjara, cambuk dan denda. Peradilan Islam dan Undang Undang Saksi Tahun 1950 telah menetapkan beberapa metode untuk validasi dokumen seperti: pengakuan, testimoni, pendapat ahli, dan sumpah, namun pendapat dari ahli masih merupakan cara utama untuk verifikasi keautentikan dan keaslian dokumen. Artikel ini juga menemukan bahwa peraturan hukum di Malaysia belum membahas sumpah sebagai alat verifikasi dokumen. Juga metodenya berbeda antara yang ada di dalam buku teks dengan Undang Undang 1950 yang lebih fokus pada kondisi dokumen dan jumlah saksi, padahal di dalam hukumnya tidak memperhitungkan jumlah saksi, hanya kondisinya saja.]